MALE AND FEMALE STUDENTS’ POLITENESS IN SRAGEN, CENTRAL JAVA - Zahra Fizty Febriadina; Sumarwati Sumarwati; Sumarlam Sumarlam (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2018)
The students' language politeness can be observed from gender perspective. The objective of this research is to describe the form of language politeness between male and female students in Vocational school. Politeness principle used Leech politeness principle (1993), focuse of this research is the form of male and female students’ politeness. This is descriptive qulitative reseacrh with sociopragmatics approach. The data are the politeness uttarances made by the student. The data are collected by using listening-free-participating-speaking (simak bebas libat cakap/SBLC) technique and data transcription. The data analyzing technique use Miles and Huberman interactive model, that consists of four steps, they are collecting data, reducing data, analizing data and verifying or conclusion drawing by pragmatics comparing methods. The result of the research shows that there is a different form of language politeness between male and female students which is reflected in politeness and impoliteness maxim. Female students’ politeness maxim are (1) tact maxim; (2) generosity maxim; and (3) agreement maxim. Male students’ impoliteness maxim are (1) generosity maxim; (2) modesty maxim; (3) agreement maxim; dan (4) the sympathy maxim.Keyword: students’ politeness, gender, Vocational School KESANTUNAN SISWA LAKI-LAKI DAN PEREMPUAN DI SRAGEN, JAWA TENGAHAbstrakKesantunan berbahasa siswa dapat dilihat dari perspektif gender. Penelitian ini bertujuan untuk mendeskripsikan bentuk kesantunan berbahasa siswa laki-laki dan perempuan dalam Sekolah Menengah Kejuruan. Prinsip kesantunan yang digunakan adalah prinsip kesantunan menurut Leech (1993), fokus penelitian pada bentuk kesantunan berbahasa siswa laki-laki dan siswa perempuan. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan sosiopragmatik. Data berupa tuturan siswa yang mencerminkan kesantunan berbahasa. Pengumpulan data menggunakan teknik simak bebas libat cakap (SBLC) dan transkripsi data. Teknik analisis data menggunakan model interaktif Miles dan Huberman yang terdiri dari empat tahap, yaitu pengumpulan data, reduksi data, analisis data dan verifikasi atau penarikan simpulan. Hasil penelitian ditemukan perbedaan bentuk kesantunan berbahasa antara siswa laki-laki dan siswa perempuan. Perbedaan tersebut tercermin dalam maksim kesantunan yang dipatuhi dan dilanggar oleh siswa. Pematuhan prinsip kesantunan siswa perempuan terdapat dalam (1) maksim kebijaksanaan; (2) maksim kedermawanan; dan (3) maksim kesepakatan. Sedangkan penyimpangan prinsip kesantunan siswa laki-laki terdapat dalam (1) maksim kedermawanan; (2) maksim kerendahhatian; (3) maksim kesepakatan; dan (4) maksim kesimpatian.Kata kunci: kesantunan berbahasa siswa, gender, Sekolah Menengah Kejuruan